The Value of Vascular Surgeons in Modern Healthcare Systems: A Systematic Review and Meta-Analysis - Ojeda, Luis Morales; Arcila, Stefania Montero; Nunes, Victor Andrade; Durate, Cristiano Marciano [UNESP]; Papi, Melina; Jacobs, Donald L; Malgor, Emily A; Malgor, Rafael D (Elsevier, 2025)
BACKGROUND: Vascular surgeons are crucial in modern health care, offering indispensable support across surgical services. Despite their clinical and economic contributions, their full value often goes unrecognized. This systematic review and meta-analysis aimed to assess the interdisciplinary and financial impact of vascular surgeons within contemporary health care systems. METHODS: A systematic search was conducted in August 2024 across MEDLINE, PubMed, the Cochrane Vascular Registers, and other databases. The studies included randomized controlled trials, cohort studies, and economic evaluations published from 2010 onward. Dual reviewer screening and data extraction followed PRISMA guidelines, and the study protocol was registered with PROSPERO (CRD42024589273). Quality assessment was performed using the Newcastle-Ottawa scale. Meta-analyses employed random effects models, with heterogeneity assessed via I2 and Cochran's Q tests. RESULTS: Of 3031 screened records, 29 studies involving 6557 patients met the inclusion criteria. Vascular surgery consultations were most frequently requested by emergency medicine (15.3%), orthopedics (14.1%), trauma (12.2%), and neurosurgery (10.1%). Hemorrhage control (16.4%) and ischemia (14.1%) were the primary reasons for consultations. Vascular surgeons performed 928 procedures, predominantly primary repairs (49.2%) and graft placements (17.7%). Multidisciplinary collaboration, particularly in surgical oncology and podiatry, significantly improved outcomes, including revascularization success in cases of acute limb ischemia and intraoperative arterial injuries (94%), decreased amputation rates, and enhanced margin-negative resections. Financial analyses revealed that vascular surgery contributes substantial work relative value units (wRVUs) and revenue, with some services generating >$130 million over 5 years. Meta-analysis identified pooled consultation proportions of 22% among urology, orthopedics, and general surgery, with significant heterogeneity (I2 = 98.7%). Meta-regression confirmed consultation volume as a significant predictor of pooled effect size. CONCLUSIONS: Vascular surgeons play a crucial role in interdisciplinary health care and are a valuable financial resource in medical services. Their participation improves surgical results, decreases complications, and enhances hospital profitability. It is essential to strategically incorporate and acknowledge vascular surgery within multidisciplinary teams and institutional planning to optimize patient care, revenue generation, and system efficiency.